2018
DOI: 10.12659/msm.910229
|View full text |Cite
|
Sign up to set email alerts
|

Silencing BRIT1 Facilitates the Abilities of Invasiveness and Migration in Trophoblast Cells

Abstract: BackgroundThe improper invasion of trophoblast cells (TC) can cause various diseases. BRCT-repeat inhibitor of hTERT expression (BRIT1) is involved in the invasion of tumors. Here, we analyzed the effects of BRIT1 on the invasion of TC.Material/MethodsThe expression of BRIT1 in JEG-3, B6Tert, and HTR8/SVneo cells was evaluated by transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blotting. The viability, invasion, and migration of HTR8/SVneo cells were measured using cell counting kit-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Xing et al found that knockdown of WNT3 expression in tumor cells significantly blocked cell proliferation, delayed cell cycle progression, and suppressed cell invasion and metastasis, accompanied by increased apoptosis [ 31 ]. In addition, increasing the expression of WNT3 accelerated the invasion and migration of trophoblast cells [ 40 ]. The results of this study revealed high expression of WNT3.…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al found that knockdown of WNT3 expression in tumor cells significantly blocked cell proliferation, delayed cell cycle progression, and suppressed cell invasion and metastasis, accompanied by increased apoptosis [ 31 ]. In addition, increasing the expression of WNT3 accelerated the invasion and migration of trophoblast cells [ 40 ]. The results of this study revealed high expression of WNT3.…”
Section: Discussionmentioning
confidence: 99%
“…Xing Z et al found that knockdown of WNT3 expression in tumor cells signi cantly blocked cell proliferation, delayed cell cycle progression and suppressed cell invasion and metastasis, accompanied by increased apoptosis [31]. In addition, increasing the expression of WNT3 accelerated the invasion and migration of trophoblast cells [40]. The results of this study revealed high expression of WNT3.…”
Section: Discussionmentioning
confidence: 50%
“…There are increasing evidences indicate that Wnt/β‐catenin is closely related to the transfer and invasion of trophoblast cells. For instance, Liu et al 27 . demonstrated that BRIT1 silencing activated the Wnt/β‐catenin pathway and accelerated the invasion and migration of trophoblast cells.…”
Section: Introductionmentioning
confidence: 99%